Association between LHβR gene variant and infertility - Elvan Yılmaz; Ayse Ozdemir; Mesut Onal; Davut Guven; Sengul Tural; Idris Kocak (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2020)
Assisted reproductive techniques have been developed for infertility related problems and to offer more treatment options with increased infertility rates. The aim of the study was to investigate the effect of Luteinizing hormone β receptor (LHβR) gene variants on outcome of In Vitro Fertilization (IVF). This study included 69 cases (29 cases with failured of IVF treatment in IVF Center of Ondokuz Mayis University Hospital by comparing with 30 healthy pregnant cases). DNA isolated from all the cases and LHβ gene was analyzed by next generation DNA sequencing method. The statistical analysis was performed by SPSS and Chi-Square analysis. There was no statistically significant difference between patients and control groups for LHβ gene exon 3 mutations of rs1056917 and rs149579838 (p>0.05). When we investigate clinical findings according to the genotype, we found that, GG genotype of rs149579838 (p=0.04, χ²=6.381) and AG genotype of rs1056917 (p=0.03, χ²=6,75) was statistically significant for primary infertile cases. Our results suggest that women who have GG genotype for rs149579838 and AG genotype for rs1056917 are under risk for primary infertility. Large scaled, prospective and randomized trails are needed to demonstrate the relationship between LHβ gene exon 3 mutations and infertility. These results should be confirmed by further and larger researches groups.